109 Morphological Changes in Chronic Subdural Hematomas Following Upfront Middle Meningeal Artery Embolization: Sequence, Timing, and Association with Outcomes. (1st March 2022) - Khorasanizadeh, MirHojjat; Chang, Yu-Ming; Enriquez-Marulanda, Alejandro; Mizuhashi, Satomi; Moore, Justin M.; Ogilvy, Christopher S.; Thoma, Ajith J.
Abstract : INTRODUCTION: Middle meningeal artery embolization (MMAE) is a novel approach for treatment of chronic subdural hematomas (cSDH). The course of morphological progression of cSDHs following MMAE is poorly understood. METHODS: Through a retrospective survey of the institutional database, cSDH cases treated by upfront MMAE, without prior/adjunctive surgical evacuation, were selected. Hematomas were categorized into 6 morphological subtypes. CT-scans were assessed for hematoma structural appearance, density, and loculations. Changes in hematoma size were quantified via 3-dimensional reconstruction for volumetric measurement. RESULTS: 52 hematomas in 45 patients treated by upfront MMAE were identified. Hematomas were followed for a mean of 92.9 days. Volume of hematomas decreased by =50% in 79.6% of cases. The overall rescue surgery rate was 9.6%. A clear sequence of morphological changes after MMAE was identified. Hematomas not conforming to this sequence (5.4%) all required rescue surgery. Hematomas were categorized into early, intermediate and late stage on this basis. Progression from early to intermediate and then to late stage took 12.7 and 30.0 days respectively on average. Volume of early/intermediate and late-stage hematomas decreased by =50% a mean of 78.2 and 47.6 days after MMAE respectively. Early/intermediate-stage hematomas showed more favorable outcomes compared to late-stage hematomas. Density of homogenous hypodense hematomas (H-SDHs) transiently increased immediately after MMAE (p<0.001). A marked decrease in density and volume 1-3 weeks after MMAE in H-SDHs was detected, lack of which indicated eventual need for rescue surgery. In H-SDHs, a baseline mean density of <20 HU, and a lower density than baseline by 1 month post-MMAE were predictors of favorable outcomes. Baseline hematoma volume, axial thickness, and midline shift were not correlated with outcomes. Loculated, trabecular, and laminar hematomas – known to have unfavorable surgical outcomes – had outcomes similar to other "surgical" hematomas. CONCLUSION: This is the first study to describe nature, sequence, and timing of morphological changes after MMAE of cSDHs, and identify structural features that can predict treatment outcomes.